Factors Affecting the Price of Curly Chili at the Producer Level in West Bandung Regency - Euis Dasipah; Nataliningsih; Titin Sriyogasari (Jurnal Penelitian Pendidikan IPA, 2024)
Fluctuations in chili prices often occur due to the uneven availability of chili supply throughout the year, so the price of chili will jump up when the supply is low. The decline in the amount of cayenne pepper crop production in West Bandung Regency is an indicator that there is a decrease on the supply side. This study aims to analyze the effect of total harvested area, production costs, and yields/production of curly red chili on the price of curly red chili at the farm level. This research uses quantitative research methods. Data analysis using multiple linear regression. The types of data in this study are secondary data and primary data. The method of determining the sample in this study is a survey method with random sampling techniques selected randomly. The total respondents were 68 farmers, so the number of samples in this study was 35 farmers and consumers. The results showed that simultaneously, there was no significant and simultaneous influence between area, production costs, and yields/production on the price of curly red chili peppers in Parongpong District. While partially independent, the independent variables (area, production costs, and yields/production) have a real effect on the price of curly red chili peppers in Parompong District